The Implementation of Blended Librarian Skill at UPI Library as a Form of Librarian Professionalism Attitude in the Informatiom Tecnology Era - Kamila, Bella Milati; Syaftina, Maulidya; Haniifah, Shafira (Edulib, 2023)
The emergence of information technology resulted in science becoming increasingly rapidly growing. Along with the increasing and adaptive capabilities and needs of users, they tend to want all information easily and quickly. This has implications and demands for greater changes in the role of librarians at the Indonesian University of Education (UPI) library. The Blended Librarian concept is an adaptation of the librarian's role as an educator as well as a collaborator in a university environment. In addition, the application of Blended Librarian Skills describes librarians as academic partners who collaborate with educators and academics in supporting the Tri Dharma of Higher Education, namely education and teaching, research, and community service. The research method was conducted by interviewing librarians at the UPI Library. The findings in the form of the effectiveness of the application of the Blended Librarian concept in the UPI Library include the competence of managers, mediators, and educators in improving the quality of librarian professionalism. Librarians collaborate proactively in advancing the teaching and learning process. Blended librarian skills become the urgency of the librarian's professionalism in realizing instructional design for learning in the information technology era.